2015
DOI: 10.1332/204986015x14332581741051
|View full text |Cite
|
Sign up to set email alerts
|

‘This is a cage for migrants’: the rise of racism and the challenges for social work in the Greek context

Abstract: Greece has been an emblematic case for the European Union's implementation of anti-immigration securitisation and externalisation. These policies have been translated into non-tolerance and intimidation towards certain populations, which, in turn, has resulted in more and more violent forms of the rejection of migration, which has become mainstream. Parallel to this are racist attacks, pogroms and acts of violence committed by neo-Nazi groups. On the other hand, a growing anti-racist movement has emerged in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Students' reflections on their education in this study (characterised by its non-prioritisation of social justice and antioppressive content, its highly -individualistic approaches and the lack of staff and resources) along with earlier observations by Ioakimidis (2008), Papadaki andPapadaki (2008), Teloni (2011) and Teloni and Mantanika (2015), reveal that students' unpreparedness and oppressive positions are produced within a network of power relations among the Department, the broader (oppressive educational) policies by the state (market-driven policies, 'Athena' plan) and the students' self. It would be wrong to cast the students as entirely the source of the uncritical attitudes revealed in this study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Students' reflections on their education in this study (characterised by its non-prioritisation of social justice and antioppressive content, its highly -individualistic approaches and the lack of staff and resources) along with earlier observations by Ioakimidis (2008), Papadaki andPapadaki (2008), Teloni (2011) and Teloni and Mantanika (2015), reveal that students' unpreparedness and oppressive positions are produced within a network of power relations among the Department, the broader (oppressive educational) policies by the state (market-driven policies, 'Athena' plan) and the students' self. It would be wrong to cast the students as entirely the source of the uncritical attitudes revealed in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Commenting on this mobilisation, Researchers and scholars have commented that social work in Greece has been traditionally carried out in a 'culture of silence', due to poor, even oppressive working conditions that include the deconstruction of welfare, the low status of social work and the historical evolution of social work as a conservative and neutral profession based on individualistic approaches to social problems (Ioakimidis, 2008;Papadaki, 2005;Teloni and Mantanika, 2015). However, a gradual radicalisation and politicisation of social work seems to be occurring in Greece (Papadaki and Papadaki, 2008;Teloni, 2011;Teloni and Mantanika, 2015) as well as inappropriate academic conditions with limited resources, staff shortages and a 'schism' between permanent educators and teaching fellows (Ioakimidis, 2008). Social work departments have the autonomy to develop their own course content; however, its efficacy to stimulate an anti-oppressive practice is questioned in the light of recent research.…”
Section: Greece In Times Of Oppression and Anti-oppressive Practicementioning
confidence: 99%
“…This change is reflected not only in the grassroots initiatives by social workers in the community (for example the community interventions of the Greek branch of Social Work Action Network) but also on the very recent politicisation of the Greek Professional Association of Social Workers (SKLE) by participating in strikes and demonstrations against austerity measures and racism (Teloni and Mantanika, 2015). Whilst these recent responses suggest an anti-oppressive and radical shift within the profession, a more collective and critical approach both in practice and education is still very limited.…”
Section: Social Work Education In Greece -A Background Notementioning
confidence: 99%
“…In relation to the content of the curricula, previous research on social work education in Greece has suggested that individualistic and uncritical approaches within the curriculum predominate (Ioakimidis, 2008;Papadaki and Papadaki, 2008;Teloni, 2011a;Teloni and Mantanika, 2015). Dedotsi et al (2016) have observed that whilst some newer modules claim to provide a more structural approach with references to multicultural work, these do not necessarily elevate students' critical consciousness and adherence to professional (anti-oppressive) values.…”
Section: Social Work Education In Greece -A Background Notementioning
confidence: 99%
“…Yet, numerous solidarity and social movements have developed across the country as a response to austerity and oppression that are participating in solidarity activities and social action. Commenting on this mobilisation, as well as Teloni and Mantanika (2015), have described new forms of grassroots social welfare and political action in Greece. For example, the Social Medical Centres expose the consequences of policy cuts in health care, develop alternative ways of intervention and engage in community action.…”
Section: Greece In Times Of Oppression and Anti-oppressive Practicementioning
confidence: 99%